2010
DOI: 10.1016/j.vaccine.2010.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting humoral and cellular immune responses and mucosal dissemination after intramuscular DNA immunization

Abstract: Naïve Indian rhesus macaques were immunized with a mixture of optimized plasmid DNAs expressing several SIV antigens using in vivo electroporation via the intramuscular route. The animals were monitored for the development of SIV-specific systemic (blood) and mucosal (bronchoalveolar lavage) cellular and humoral immune responses. The immune responses were of great magnitude, broad (Gag, Pol, Nef, Tat, Vif), long-lasting (up to 90 weeks post 3rd vaccination) and were boosted with each subsequent immunization, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 78 publications
9
52
0
1
Order By: Relevance
“…In contrast to nonpersistent viral vectors, which induce cellular responses with central memory phenotype, the bias induced by CMV vectors toward cellular responses with EM phenotype was considered a substantial advantage, because EM cells react immediately upon encountering the antigen. Similarly, the cellular responses induced in the vaccinated macaques described in the present study were mainly EM T cells (both CD28 + CCR7 − and CD28 − CCR7 − ), and we have previously reported that these cellular responses efficiently migrate into mucosal sites, where they persist for long periods of time after the last vaccination (29).…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to nonpersistent viral vectors, which induce cellular responses with central memory phenotype, the bias induced by CMV vectors toward cellular responses with EM phenotype was considered a substantial advantage, because EM cells react immediately upon encountering the antigen. Similarly, the cellular responses induced in the vaccinated macaques described in the present study were mainly EM T cells (both CD28 + CCR7 − and CD28 − CCR7 − ), and we have previously reported that these cellular responses efficiently migrate into mucosal sites, where they persist for long periods of time after the last vaccination (29).…”
Section: Discussionsupporting
confidence: 83%
“…ϩ Tem responses that can be expanded by a heterologous boost with a viral vector (34,69,70). Our studies further demonstrated that DREP induced both Tcm and Tem and that a protein boost preserved Tcm proportions, whereas boosting with MVA preferentially expanded Tem subpopulations.…”
Section: Discussionsupporting
confidence: 55%
“…We have demonstrated that HIV/SIV pDNA vaccines induce responses, including CE-induced (X. Hu, A. Valentin, and B.K. Felber, unpublished observations) responses, which efficiently disseminate to mucosal tissues (39,54). In addition, the recent demonstration of therapeutic efficacy of a human papilloma virus vaccine delivered by DNA or electroporation in a Phase IIB randomized study in humans (55)(56)(57) demonstrates the efficacy of a pDNA platform in inducing mucosal T cell responses in humans.…”
Section: Discussionmentioning
confidence: 89%
“…We previously reported that therapeutic SIV pDNA vaccination induces potent immune responses (as high as ∼10% of T cells in blood) able to reduce viremia by 1 log following interruption of ART in SIV mac251 -infected Indian rhesus macaques (58,59). Importantly, some animals maintained reduced viral a loads for more than 3 y, indicating there is a long-lasting effect of the vaccine-induced T cell responses, another hallmark of the pDNA platform (32,54). Together, these data provide a proof-ofconcept in support of adding pDNA vaccination, and in particular CE followed by CE+gag pDNA booster vaccination to cART regimens to augment potent virus-specific immune responses.…”
Section: Discussionmentioning
confidence: 99%